Identification of viral protein R of human immunodeficiency virus-1 (HIV) and interleukin-6 as risk factors for malignancies in HIV-infected individuals: A cohort study - Matsunaga, Akihiro; Ando, Naokatsu; Yamagata, Yuko; Shimura, Mari; Gatanaga, Hiroyuki; Oka, Shinichi; Ishizaka, Yukihito (PloS one, 2024)
Despite effective antiretroviral therapy, patients with human immunodeficiency virus type-1 (HIV) suffer from a high frequency of malignancies, but related risk factors remain elusive. Here, we focused on blood-circulating viral protein R (Vpr) of HIV, which induces proinflammatory cytokine production and genotoxicity by exogenous functions. A total 404 blood samples of HIV patients comprising of 126 patients with malignancies (tumor group) and 278 patients without malignancies (non-tumor group), each of 96 samples was first selected by one-to-one propensity score matching. By a detergent-free enzyme-linked immunosorbent assays (detection limit, 3.9 ng/mL), we detected Vpr at a higher frequency in the matched tumor group (56.3%) than in the matched non-tumor group (39.6%) (P = 0.030), although there was no different distribution of Vpr levels (P = 0.372). We also detected anti-Vpr immunoglobulin (IgG), less frequently in the tumor group compared with the tumor group (22.9% for tumor group vs. 44.8% for non-tumor group, P = 0.002), and the proportion of patients positive for Vpr but negative of anti-Vpr IgG was significantly higher in the tumor group than in the non-tumor group (38.6% vs. 15.6%, respectively, P < 0.001). Additionally, Interleukin-6 (IL-6), the levels of which were high in HIV-1 infected patients (P < 0.001) compared to non-HIV-infected individuals, was significantly higher in advanced cases of tumors (P < 0.001), and IL-6 level was correlated with Vpr in the non-tumor group (P = 0.010). Finally, multivariate logistic regression analysis suggested a positive link of Vpr with tumor occurrence in HIV patients (P = 0.002). Vpr and IL-6 could be risk factors of HIV-1 associated malignancies, and it would be importance to monitor these molecules for well managing people living with HIV-1.